Tillering and dry matter accumulation in individual plants of oat with different moments of defoliation (Semiárida, 2020)
The objective of this study was to evaluate, at individual plant level, the effect of early defoliation on the dynamics of tillering and dry matter (O M) accumulation in oat (Avena byzantina e. Koch.) cv. Milagros INTA. The study was carried out at Santa Rosa (La Pampa, Argentina) during the 2007 growing season with oat seeds sowed on March 4. The treatments consisted of a control (without defoliation) and two initial defoliation times, and three harvest dates. The beginning of defoliation was established according the number of expanded leaves: three (early) and six (tillering). The experimental design was completely randomized with a factorial arrangement of treatments (defoliation x harvest date) and three replicates. Defoliation treatments were generated on April 5 (early) and on May 3 (tillering) by cuts to a height of 5 cm. The dynamics of tiller density and DM accumulation were evaluated in three dates: one early on June, and the other two with a 30 day frecuency. The tiller density and DM accumulation of individual oat plants with early defoliation and without defoliation showed a similar pattern (p>0.05). On contrary, plants with late defoliation showed lower values (p
Keywords: oat; early defoliation; tillering; dry matter accumulation